夏季楚科奇海河水与海冰融化水组分的空间变化特征 - 童金炉; 陈敏; 潘红; 杨伟锋; 张润; 郑敏芳; 邱雨生 (2014)
通过对2008年夏季楚科奇海水氧同位素组成的分析,运用S、δ18 O的质量平衡关系计算出河水组分和海冰融化水组分的份额,揭示出楚科奇海河水和海冰融化水组分的空间变化规律,并探讨其影响因素。楚科奇海河水组分的份额介于1.9%~18.4%之间,呈现随深度增加而降低的趋势;河水组分积分高度的变化范围为1.3~16.6M,平均为(4.8±4.0)M。河水组分份额与积分高度均呈现东高西低、北强南弱的特征,与太平洋入流东侧为富含河水组分的阿拉斯加沿岸流、西侧为低河水组分的白令海陆架水,以及北部海域受波弗特流涡埃克曼辐聚作用的影响有关。海冰融化水份额呈现随深度增加而降低的趋势,20~30M以深受到冬季海冰形成时所释放盐卤水的明显影响。海冰融化水积分高度的变化范围为-3.2~1.7M,平均值为(-0.3±1.2)M,其空间分布呈现东低西高、南强北弱的特征,与太平洋入流输入通量的时间变化以及输入路径的西偏有关。 On the basis of the measured oxygen isotopic composition of seawater,the Sandδ18 O mass balance was employed to determine the fraction of river water and sea-ice melted water in Chukchi Sea in summer 2008.The spatial patterns of river water and sea-ice melted water were revealed and the affecting factors were disccussed.The fractions of river water decreased with the increasing depth,with a range from 1.9%to 18.4%.The integrated heights of river water(IfR)were 1.3~16.6m,with an average of(4.8±4.0)m.IfRshowed a spatial characteristic with high values in the east and north and low values in the west and south.This spatial variation of river water was ascribed to the difference amount of river water carried by the Pacific inflows(e.g.,high river water components in the Alaska Current Water and low river water components in the Bering Shelf water),the pathway of the Pacific inflows and the Ekman pumping of Beaufort Gyre.The fractions of sea-ice melted water decreased dramaticly with the increasing depth.A negative value was observed at depth of about 20 mto 30m.The integrated heights of sea-ice melted water(IfI)were from-3.2mto 1.7m,with an average of(0.3±1.2)m.IfIwas higher in the west and south,but lower in the east and north.The spatial variation of sea-ice melted water was attributed to the strength and time of the Pacific inflows,as well as the topographically impact which diverted the Pacific inflow westward. 南北极环境综合考察与评估专项(CHINARE2014-03-04-03;CHINARE2014-04-03-05); 海洋公益性行业科研专项(201105022-4); 国家自然科学基金杰出青年基金项目(41125020)